Redesign of the prison defense model for adults deprived of liberty in the new criminal procedure system - Lidebinsky, Sofía (Journal Studies of Public Policy, 2016)
This study case was to redesign aspects of the “Programa de Defensa Penal Pública Penitenciaria” from an analysis of its original design and current operation, using the methodology of logical framework. The research question sought to check if this program helps to strengthen the access to justice for convicted persons deprived of liberty. The study used interviews and subsequent analysis of the key actors of this program from the Defensoría Penal Pública and Gendarmería de Chile. The vision of both institutions is crucial to detect problems and successes on the implementing of the program, in order to propose some changes and improvements. A workshop with convicted and the analysis of interviews in three regions on operation, were made to know the perception of the beneficiaries of this program.